2015
DOI: 10.1146/annurev-resource-100814-125123
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks in Developing Countries

Abstract: Social networks function as an important safety net in developing countries, which often lack formal financial instruments. Such networks are also an important source of information in developing countries with relatively low access to the Internet and literacy rates. We review the empirical literature that uses explicit social network data collected in developing countries. We focus on social networks as conduits for both monetary transfers and information. We also briefly discuss the network-formation litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 116 publications
1
37
0
Order By: Relevance
“…(). Finally, we do not survey findings on the size, magnitude or heterogeneity of the social effects found in applied economics: other reviews more than amply cover these, for example, Epple and Romano () and Sacerdote () provide surveys of peer effects in education, while Chuang and Schechter () provide a survey of applied work on networks in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…(). Finally, we do not survey findings on the size, magnitude or heterogeneity of the social effects found in applied economics: other reviews more than amply cover these, for example, Epple and Romano () and Sacerdote () provide surveys of peer effects in education, while Chuang and Schechter () provide a survey of applied work on networks in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the activity participants, the limited circulation of content-related themes suggested that the main messages resonated with more privileged lifestyles irrespective of our efforts to translate and convey them in a way that is meaningful for the broader rural population (similar to core-periphery tensions raised by Broom, et al [34]). A further complication for the diffusion of the messages was that people might not deem information about drug resistance a personal priority [4,35], 11 and the benefit of slowing the development of drug resistant bacteria lacks a clear demonstration effect [24]. If these arguments hold, then new ideas about antibiotic use would remain passive unless they threaten people personally (or: we would need to combine the content with "a spark").…”
Section: Discussionmentioning
confidence: 99%
“…The one-off activity in Salavan was designed to cover half a day of interactive sessions for 25 to 40 people. 3 We selected well-known individuals from the across each village, expecting that they would inform other villagers about the content of the activity (corresponding to approaches of targeting opinion leaders [24,25]).…”
Section: Intervention (Public Engagement Activity)mentioning
confidence: 99%
“…The one-off activity in Salavan was designed to cover half a day of interactive sessions for 25 to 40 people. 4 We selected well-known individuals from the across each village, expecting that they would inform other villagers about the content of the activity (corresponding to approaches of targeting opinion leaders [24,25]).…”
Section: Methodsmentioning
confidence: 99%